Money market uncertainty and retail interest rate fluctuations: A cross-country comparison - Burkhard Raunig; Johann Scharler (Johannes Kepler University of Linz, Department of Economics, 2007)
This paper analyzes empirically the relationship between money market uncertainty and unexpected deviations in retail interest rates in a sample of 10 OECD countries. We find that, with the exception of the US, money market uncertainty has only a modest impact on the conditional volatility of retail interest rates. Even for the US we find that the effects of money market uncertainty are spread out over time. Our results are consistent with the hypothesis that banking relationships include implicit insurance arrangements and thereby reduce uncertainty.
Keywords: E43; G21; 330; Interest Rate Pass-Through; Relationship Banking; Conditional Volatility; Transmissionsmechanismus; Retail Banking; Zins; Volatilität; Kreditgeschäft; OECD-Staaten